2016
DOI: 10.3390/ijms17071019
|View full text |Cite
|
Sign up to set email alerts
|

The NAD-Dependent Deacetylase Sirtuin-1 Regulates the Expression of Osteogenic Transcriptional Activator Runt-Related Transcription Factor 2 (Runx2) and Production of Matrix Metalloproteinase (MMP)-13 in Chondrocytes in Osteoarthritis

Abstract: Aging is one of the major pathologic factors associated with osteoarthritis (OA). Recently, numerous reports have demonstrated the impact of sirtuin-1 (Sirt1), which is the NAD-dependent deacetylase, on human aging. It has been demonstrated that Sirt1 induces osteogenic and chondrogenic differentiation of mesenchymal stem cells. However, the role of Sirt1 in the OA chondrocytes still remains unknown. We postulated that Sirt1 regulates a hypertrophic chondrocyte lineage and degeneration of articular cartilage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 27 publications
(51 reference statements)
2
31
2
1
Order By: Relevance
“…These findings indicate that Sirt-1 activity, which is downregulated by several cellular stresses, may directly influence the expression of Runx2 in chondrocytes, affecting the enzymatic degeneration of articular cartilage and osteophyte formation in OA. We concluded that Sirt-1-regulated-Runx2 expression could control the production of MMP-13 and osteophyte formation by OA chondrocytes [18]. We postulate that Sirt1 activity in chondrocytes could be an important contributing factor in the pathogenesis and pathophysiology of OA.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…These findings indicate that Sirt-1 activity, which is downregulated by several cellular stresses, may directly influence the expression of Runx2 in chondrocytes, affecting the enzymatic degeneration of articular cartilage and osteophyte formation in OA. We concluded that Sirt-1-regulated-Runx2 expression could control the production of MMP-13 and osteophyte formation by OA chondrocytes [18]. We postulate that Sirt1 activity in chondrocytes could be an important contributing factor in the pathogenesis and pathophysiology of OA.…”
Section: Introductionmentioning
confidence: 83%
“…Articular cartilage explants were cut into small pieces, washed with phosphate-buffered saline (PBS) and digested with 1.5 mg/mL collagenase B (Sigma, St. Louis, MO, USA) in Dulbecco's modified Eagle's medium (DMEM) (Sigma) overnight on a shaking platform at 37°C. Isolated chondrocytes were collected following centrifugation, washed three times with PBS, resuspended and cultured in DMEM supplemented with 10% heat-inactivated foetal calf serum (FCS), 2 mM L-glutamine, 25 mM HEPES (2[4-(2-hydroxyethyl)-1-piperazinyl] ethane sulfonic acid), and 100 U/mL penicillin and streptomycin at 37°C in a humidified atmosphere of 95% air and 5% CO 2 as previously reported [18]. …”
Section: Human Chondrocyte Culturesmentioning
confidence: 99%
See 3 more Smart Citations